Synthesis of the Heteropolysaccharide O Antigen of Escherichia coli O52 Requires an ABC Transporter: Structural and Genetic Evidence - Feng, Lu (American Society for Microbiology, 2004)
The structural and genetic organization of the Escherichia coli O52 O antigen was studied. As identified by sugar and methylation analysis and nuclear magnetic resonance spectroscopy, the O antigen of E. coli O52 has a partially O-acetylated disaccharide repeating unit (O unit) containing d-fucofuranose and 6-deoxy-d-manno-heptopyranose, as well as a minor 6-deoxy-3-O-methylhexose (most likely, 3-O-methylfucose). The O-antigen gene cluster of E. coli O52, which is located between the galF and gnd genes, was found to contain putative genes for the synthesis of the O-antigen constituents, sugar transferase genes, and ABC-2 transporter genes. Further analysis confirmed that O52 employs an ATP-binding cassette (ABC) transporter-dependent pathway for translocation and polymerization of the O unit. This is the first report of an ABC transporter being involved in translocation of a heteropolysaccharide O antigen in E. coli. Genes specific for E. coli O52 were also identified.